A Systematic Review of the Cardiovascular Manifestations and Outcomes in the Setting of Coronavirus-19 Disease. Issue 14 (November 2020) - Thakkar, Samarthkumar; Arora, Shilpkumar; Kumar, Ashish; Jaswaney, Rahul; Faisaluddin, Mohammed; Ammad Ud Din, Mohammad; Shariff, Mariam; Barssoum, Kirolos; Patel, Harsh P; Nirav, Arora; Jani, Chinmay; Patel, Kripa; et al.
The impact of coronavirus disease, 2019 (COVID-19), has been profound. Though COVID-19 primarily affects the respiratory system, it has also been associated with a wide range of cardiovascular (CV) manifestations portending extremely poor prognosis. The principal hypothesis for CV involvement is through direct myocardial infection and systemic inflammation. We conducted a systematic review of the current literature to provide a foundation for understanding the CV manifestations and outcomes of COVID-19. PubMed and EMBASE databases were electronically searched from the inception of the databases through 27 April 2020. A second literature review was conducted to include major trials and guidelines that were published after the initial search but before submission. The inclusion criteria for studies to be eligible were case reports, case series, and observation studies reporting CV outcomes among patients with COVID-19 infection. This review of the current COVID-19 disease and CV outcomes literature revealed a myriad of CV manifestations with potential avenues for treatment and prevention. Future studies are required to understand on a more mechanistic level the effect of COVID-19 on the myocardium and thus provide avenues to improve mortality and morbidity.